RAFT Polymerization of Styrene with Potassium Ethylxanthate as the Chain Transfer Agent - Xu, Xinmeng; Xu, Xiang; Zeng, Yanning; Zhang, Faai (Journal of Research Updates in Polymer Science, 2020)
Using potassium ethylxanthate as the chain transfer agent, 2,2’-azobis(isobutyronitrile) (AIBN) as the initiator, reversible addition-fragmentation chain transfer (RAFT) polymerization of styrene was carried out. The influences of reaction temperature, reaction time, and the amounts of the initiator and chain transfer agent on the RAFT polymerization were investigated in terms of monomer conversion, average number molecular weight (Mn) and molecular weight distribution (Ð) of the obtained polymer. Monomer conversion and the Mn of the obtained polystyrene (PS) improved with an increase in the reaction temperature, and the polymerization kinetics exhibited a highly linear relationship, indicating a first-order reaction. When the amounts of the initiator and chain transfer agent were increased, it led to a decreased Mn of the produced PS. Meanwhile, the Ð of the PS was in a relatively narrow range (1.42-1.89). The chain-end functionality was further demonstrated by adding methyl methacrylate to the PS.